2012
DOI: 10.4071/cicmt-2012-tha41
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial reaction of LTCC/NiCuZn ferrites in multilayer composites

Abstract: In this study, the cofiring behavior and interfacial interaction between a low dielectric constant LTCC material and NiCuZn ferrites at 900°C were studied using XRD, dilatometer, SEM, EPMA and TEM. It was observed that the delamination occurred at the interface between LTCC and NiCuZn ferrites added with Bi2O3. It may be due to the Bi enriched at the interface and diffused into LTCC, which shifted the densification curve of LTCC towards low temperature, and hence resulted in the shrinkage mismatch between LTCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The NiCuZn ferrite is composed mainly of nickel, copper, zinc and iron. In our previous study [10], the chemical composition across the interface between NiCuZn ferrites and LTCC after cofiring at 900 • C for 2 h was investigated and observed that no obvious element inter-diffusion of Ni, Zn, Fe, Al and Si was observed at the interface. Only a small concentration of copper ions from the ferrite can diffuse into the LTCC at a distance of around 10 m, which is consistent with the observations of Lee et al [11].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NiCuZn ferrite is composed mainly of nickel, copper, zinc and iron. In our previous study [10], the chemical composition across the interface between NiCuZn ferrites and LTCC after cofiring at 900 • C for 2 h was investigated and observed that no obvious element inter-diffusion of Ni, Zn, Fe, Al and Si was observed at the interface. Only a small concentration of copper ions from the ferrite can diffuse into the LTCC at a distance of around 10 m, which is consistent with the observations of Lee et al [11].…”
Section: Methodsmentioning
confidence: 99%
“…The cofiring behavior and interfacial structure of LTCC/NiCuZn ferrite laminates were recently investigated [2,[10][11][12][13]. In our previous study large pores and air gaps occurred at the interface between NiCuZn ferrites containing Bi 2 O 3 and LTCC after cofiring at 900 • C for 2 h. This is due to widening of the shrinkage mismatch between NiCuZn ferrites and LTCC resulting from Bi 2 O 3 in NiCuZn ferrites diffusion into LTCC.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation